(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
most prevalent malignancy among all forms of thyroid cancers is papillary thyroid carcinoma (PTC). This is one of the few cancers that is rapidly increasing. The prognosis is excellent with an overall 10-year survival rate of 90%. However, few patients show poor prognosis and disease recurrence. Recently genetic mutations have been considered to be contributing factors to the clinical and behavioral metastatic risk factors. The most common genetic mutation involved in PTC is BRAF(V600E) mutation. The objective of this study was to see outcome of PTC patients associated with BRAF mutation after radioactive iodine ablation (RAIA). Methodology: This prospective cohort study was carried out at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS). A total of 63 patients with PTC after thyroidectomy were referred to NINMAS for RAIA were included in this study. All the necessary information was collected. Clinical staging of thyroid cancer was classified according to the Tumor-node-metastasis (TNM) classification of AJCC 8th edition; 2018. All of them were tested for BRAF(V600E) mutation. BRAF mutation-negative groups were selected to match the patients with BRAF positive mutation. Patients underwent a visit three months interval after RAIA evaluating thyroglobulin (Tg) levels, anti-thyroglobulin antibody (Anti Tg Ab) levels, neck ultrasound (US), whole-body 131I scan. Patients were given to repeated radioiodine with a higher dose than the previous dose based on disease stage, recurrence, and metastasis. Tg level <2 ng/dl was considered disease-free (DF) and Tg > 2 ng/dl was considered persistence of disease (PD) based on Tg. Progression of disease was considered in case of rising Tg, local recurrence, positive post-therapy scan (RxWBS) or diagnostic whole-body scan (DxWBS). The outcome based on metastasis, recurrence, or progression of the disease of these patients was observed. Result: A total of 63 patients, male 25 (39.7%) and female 38(60.3%), were included in this study. Among them, 23 (36.51%) were BRAF (V600E) positive, and 40 (63.49%) were negative. After one year follow up 23(36.51%) were disease free; 4(17.39%) were BRAF positive, and 19(82.61%) were BRAF negative; 38(60.32%) showed persistent disease, 17(44.74%) were BRAF positive and 21(55.26%) were negative; 2(3.17%) BRAF positive patients showed disease progression and; p-value was 0.016 which was statistically significant. Conclusion: In this study, patients with positive BRAF mutation showed aggressive presentation and poorer outcome. BRAF mutation negative patients showed higher rate of disease-free condition. BRAF analysis in PTC patients provides important prognostic value. These patients might be benefited by receiving more intensive management and frequent follow up. Bangladesh J. Nuclear Med. 27(2): 173-179, 2024